Vendor Managed Inventory (VMI): evidences from lean deployment in healthcare - Guimarães, M.; Crespo de Carvalho, J.; Maia, A. (Strategic Outsourcing: An International Journal, 2013)
Purpose – Understanding how VMI benefits serve lean purposes in healthcare and why its outcomes can be difficult to achieve in healthcare settings is the main purpose of this study. Design/methodology/approach – An in-depth case study of VMI is presented in the perspective of the downstream member, a public general multi-site hospital, operating as a small scale consolidated service centre in terms of material management, exploring such dimensions as: VMI benefits, risks, barriers and enablers. Findings – Despite some unawareness of VMI benefits in healthcare, it can present a waste reduction solution not only in costs but in the quality of care for freeing clinical professionals to clinical tasks, among other savings. The multiple benefits are better explored, as in any relationship building, by investing in partnership creation and overcoming the idiosyncratic barriers of the healthcare sector. Research limitations/implications – Although findings of a single case study are difficult to generalize, the protocol and methodology presented allow replication in other units of analysis with the same inclusion criteria. Practical implications – This paper brings the lean deployment discussion out of the organization's boundaries, showing the interconnections and pointing to the need for future work that would allow healthcare managers to build a lean supply chain. Originality/value – By considering VMI an outsourcing alternative, this paper identifies the lean thinking intent behind such options and enhances the idiosyncratic difficulties in full deployment in the healthcare sector, a less studied setting.